Transformational Leadership: Investing in Followers’ Development - Richard, Hendjena Tchanaga; Simankane, Tapologo (Journal of Education and Society, 2020)
This paper aims to demonstrate that transformational leadership that is foundational in developing leaders to benefit of the followers, the leaders themselves and the organization. Transformational leadership is a theory where a leader works with teams to identify needed change, creating a vision to guide the change through inspiration, executing the change, and executing it in tandem with committed members of a group; an integral part of the Full Range Leadership Model. Transformational leadership theory is used worldwide in the development of followers. To face the need of followers’ development, transformational leadership theory seems to be adequate. This paper reviewed qualitative works on the use of transformational leadership theory in relationship with the development of followers. Reviewed literatures revealed that transformational leaders are motivators, stimulators of innovation and creativity, and they pay special attention to each follower’ need for achievement and growth. The authors focused on the four components: idealized influence, inspirational motivation, intellectual stimulation and individualized consideration. Ultimately, researchers determined that transformational leadership requires leaders to demonstrate specific skills focused on followers’’ development. Transformational leaders experience success in empowering followers when they allow followers to participate and make input in organizational performance.